A historical analysis of surgery performed between 1941 and 1942 at the Bangour Maxillofacial and Plastic Surgery Unit, Scotland. Issue 9 (September 2021) - Stewart, Calum K.; Nicolaou, Marios; Dheansa, Baljit; Williams, Louise A.; Demetriades, Andreas K.
Summary: In 1939, Bangour Emergency Medical Services Hospital was built as an annexe to Edinburgh War Hospital. The Maxillofacial and Plastic Surgery Unit opened in 1941, one of the several set-ups built with the support of Sir Harold Gillies, to ensure a service with specialist skills throughout Great Britain. The unit was led by Alexander Burns Wallace, who had to rapidly adapt the service to reflect the patterns of injury reflected by the more modern warfare practiced in the Second World War, while also incorporating techniques that were, at the time, revolutionary. Although much has been written about other units, Bangour's activity revealed through its case histories' highlights that plastic surgery was developing in parallel throughout Britain. The influence of Sir Harold Gillies was clear, and his input to support the fledgling service serves as an important aspect of the newly developing specialty of plastic surgery: collaboration and sharing of knowledge. This paper analyses the work of the Maxillofacial and Plastic Surgery Unit at Bangour General Hospital in Scotland between 1941 and 1942 and demonstrates its historical significance, as well as its relevance to current practice. Ninety-two case notes from the unit recently became accessible. These were analysed and four were selected for review in this study. These cases were selected as they were well-documented with photographs and good examples of the work performed at the unit in order to highlight the innovative, creative and complicated work carried out at the Unit.